{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Fundamentals of Microelectronics

This preview shows pages 1–23. Sign up to view the full content.

3.1 (a) I X = braceleftBigg V X R 1 V X < 0 0 V X > 0 V X (V) I X Slope = 1 /R 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
3.2 I X = braceleftBigg V X R 1 V X < 0 0 V X > 0 Plotting I X ( t ), we have 0 - V 0 /R 1 I X ( t ) for V B = 1 V (Solid) - π/ω 0 π/ω t - V 0 0 V 0 V X ( t ) (Dotted)
3.3 I X = braceleftBigg 0 V X < V B V X V B R 1 V X > V B Plotting I X vs. V X for V B = - 1 V and V B = 1 V, we get: - 1 1 V X (V) I X V B = - 1 V V B = 1 V Slope = 1 /R 1 Slope = 1 /R 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
3.4 I X = braceleftBigg 0 V X < V B V X V B R 1 V X > V B Let’s assume V 0 > 1 V. Plotting I X ( t ) for V B = - 1 V, we get 0 ( V 0 - V B ) /R 1 I X ( t ) for V B = - 1 V (Solid) - π/ω 0 π/ω t - V 0 0 V B V 0 V X ( t ) (Dotted) Plotting I X ( t ) for V B = 1 V, we get
0 ( V 0 - V B ) /R 1 I X ( t ) for V B = 1 V (Solid) - π/ω 0 π/ω t - V 0 0 V B V 0 V X ( t ) (Dotted)

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
3.5 I X = braceleftBigg V X V B R 1 V X < 0 V X > 0 Plotting I X vs. V X for V B = - 1 V and V B = 1 V, we get: - 1 V X (V) - 1 /R 1 1 /R 1 I X Slope = 1 /R 1 Slope = 1 /R 1 I X for V B = - 1 V I X for V B = 1 V
3.6 First, note that I D 1 = 0 always, since D 1 is reverse biased by V B (due to the assumption that V B > 0). We can write I X as I X = ( V X - V B ) /R 1 Plotting this, we get: V B V X (V) I X Slope = 1 /R 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
3.7 I X = braceleftBigg V X V B R 1 V X < V B V X V B R 1 bardbl R 2 V X > V B I R 1 = V X - V B R 1 Plotting I X and I R 1 for V B = - 1 V, we get: - 1 V X (V) I X I X for V B = - 1 V I R 1 for V B = - 1 V Slope = 1 /R 1 Slope = 1 /R 1 + 1 /R 2 Plotting I X and I R 1 for V B = 1 V, we get:
1 V X (V) I X I X for V B = 1 V I R 1 for V B = 1 V Slope = 1 /R 1 Slope = 1 /R 1 + 1 /R 2

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
3.8 I X = braceleftBigg 0 V X < V B R 1 + R 2 R 1 V X R 1 + V X V B R 2 V X > V B R 1 + R 2 R 1 I R 1 = braceleftBigg V B R 1 + R 2 V X < V B R 1 + R 2 R 1 V X R 1 V X > V B R 1 + R 2 R 1 Plotting I X and I R 1 for V B = - 1 V, we get: V B R 1 + R 2 R 1 V X (V) V B R 1 + R 2 - V B /R 2 I X for V B = - 1 V I R 1 for V B = - 1 V Slope = 1 /R 1 Slope = 1 /R 1 + 1 /R 2 Plotting I X and I R 1 for V B = 1 V, we get:
V B R 1 + R 2 R 1 V X (V) V B R 1 + R 2 I X for V B = 1 V I R 1 for V B = 1 V Slope = 1 /R 1 Slope = 1 /R 1 + 1 /R 2

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
3.9 (a) V out = braceleftBigg V B V in < V B V in V in > V B - 5 - 4 - 3 - 2 - 1 0 1 2 3 4 5 V in (V) 0 1 2 3 4 5 V out (V) Slope = 1 (b) V out = braceleftBigg V in - V B V in < V B 0 V in > V B
- 5 - 4 - 3 - 2 - 1 0 1 2 3 4 5 V in (V) - 7 - 6 - 5 - 4 - 3 - 2 - 1 0 1 2 V out (V) Slope = 1 (c) V out = V in - V B - 5 - 4 - 3 - 2 - 1 0 1 2 3 4 5 V in (V) - 7 - 6 - 5 - 4 - 3 - 2 - 1 0 1 2 3 V out (V) Slope = 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
(d) V out = braceleftBigg V in V in < V B V B V in > V B - 5 - 4 - 3 - 2 - 1 0 1 2 3 4 5 V in (V) - 5 - 4 - 3 - 2 - 1 0 1 2 V out (V) Slope = 1 (e) V out = braceleftBigg 0 V in < V B V in - V B V in > V B
- 5 - 4 - 3 - 2 - 1 0 1 2 3 4 5 V in (V) 0 1 2 3 V out (V) Slope = 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
3.11 For each part, the dotted line indicates V in ( t ), while the solid line indicates V out ( t ). Assume V 0 > V B . (a) V out = braceleftBigg V B V in < V B V in V in > V B - π/ω π/ω t - V 0 V B V 0 V out ( t ) (V) (b) V out = braceleftBigg V in - V B V in < V B 0 V in > V B
- π/ω π/ω t - V 0 - V B - V 0 V B V 0 V out ( t ) (V) (c) V out = V in - V B - π/ω π/ω t - V 0 - V B - V 0 V 0 - V B V B V 0 V out ( t ) (V)

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
(d) V out = braceleftBigg V in V in < V B V B V in > V B - π/ω π/ω t - V 0 V B V 0 V out ( t ) (V) (e) V out = braceleftBigg 0 V in < V B V in - V B V in > V B
- π/ω π/ω t - V 0 V 0 - V B V B V 0 V out ( t ) (V)

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
3.12 For each part, the dotted line indicates V in ( t ), while the solid line indicates V out ( t ). Assume V 0 > V B .
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

Page1 / 90

ch03sol - 3.1(a IX = VX R1 0 VX < 0 VX > 0 IX VX(V Slope =...

This preview shows document pages 1 - 23. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online